Framework for Analysis of Criminal Acts Committed by Children Against Child Victims Based on Restorative Justice - Rahmad, Rahmad; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Children are the next generation of the nation who are vulnerable to becoming victims or perpetrators of sexual crimes due to lack of protection, supervision, and adequate moral education. Children as perpetrators of sexual abuse require a more humanistic legal approach through restorative justice in accorandce with the principles of the Child Protection Law and the Child Criminal Justice System. The purpose of this study is to examine the regulation of criminal acts of sexual abuse by child perpetrators against child victims and to analyze the ideal regulation of criminal acts of sexual abuse by child perpetrators against child victims. The approach method used in compiling the thesis is normative legal research.Specifications in this studydescriptive analysis.The theories used include the theory of legal certainty and the theory of restorative justice. The results of this study are (1)Regulation of criminal acts of child molestation against child victims in Indonesia has been regulated in the Criminal Code, the Child Protection Law, and the Child Protection and Child Protection Law, with the aim of providing protection for children both as victims and as perpetrators. Although child perpetrators of child molestation can be subject to criminal responsibility, the Indonesian legal system still requires an approach that upholds children's rights, including rehabilitation efforts through the child criminal justice system. However, Article 7 paragraph (2) of the Child Protection and Child Protection Law limits the application of diversion, so that child perpetrators in criminal acts of child molestation cannot be diverted, legal uncertainty in the principle of child protection. Therefore, although existing regulations have guaranteed legal protection, a review is needed to align the objectives of criminal punishment with the restorative justice approach for children. (2) The ideal regulation of criminal acts of child molestation against child victims in the future must be directed at a restorative justice-based approach that guarantees the protection of children's rights. Lessons from the English, German, and Dutch legal systems show that child punishment can be carried out in a humane manner by emphasizing rehabilitation. The juvenile criminal law system in Indonesia through the SPPA Law needs to be revised to provide space for settlement outside the courts, including for cases that carry a criminal sentence of more than seven years, such as molestation, which is currently excluded from diversion. In addition, the government also needs to reconstruct Article 140 paragraph (2) of the Criminal Procedure Code so that it becomes the legal basis for terminating prosecution with a restorative justice approach, to ensure that the principle of "the best interests of the child" remains the main priority in the national criminal justice system.